Influência da retirada de digesta abomasal, para estudos de digestão parcial, sobre a digestibilidade aparente de nutrientes com bovinos - Sampaio, Alexandre Amstalden Moraes [UNESP]; De Figueiredo Vieira, Paulo [UNESP]; De Oliveira Ciconelli, Marcelo Ribeiro; Dal Secco De Oliveira, Mauro [UNESP]; Cattelan, José Wanderley [UNESP]; Da Graça Macoris, Delphim [UNESP] (My University, 1997)
The objective of this trial, using 21 abomasal fistulated bovines, eight months of age and 187 kg of liveweight, was to evaluate the digestibility coefficients of diets containing different protein sources (dry yeast, urea, and cottonseed meal) used in ruminant feeding. The analyses of digestibility coefficients took into account the withdrawal or not of abomasal digesta (phases 2 and 1, respectively). There was an increase on the digestibility coefficients of crude protein (52.7 to 55.0%), when abomasal digesta was withdrawn. Therefore, it is important that the collection of abomasal digesta in ruminal digestion studies be collected in different periods for studies of total digestion. The ingestion of nutrients/MSU and digestible nutrients/MSU was not affected, independent of abomasal digesta withdrawal.
Influence of removal of abomasal digesta for studies of partial digestion on the apparent digestibility of nutrients with bovines
Keywords: Abomasal digesta; Bovine; Digestibility; Protein sources